"I Don't Want People to Forget the Sentence": An Interview with Kiese Laymon. (9th January 2019) - Brown, Meghan
Abstract: In this interview, author Kiese Laymon discusses his novel Long Division (2013) and his short story collection How to Slowly Kill Yourself and Others in America (2013). His work highlights issues of race, gender, class, and education in the United States, and he explains the role that music, memory, and cultural history play in his writing. Laymon talks about his connection to his hometown of Mississippi and the American South, as well as his work as an educator in professorships at Vassar College, the University of Iowa, and his current position at the University of Mississippi. This interview illuminates his work both on the page and off, highlighting both his writing and his activism. Laymon has published pieces in Esquire, Colorlines, The New York Times, and Vanity Fair, and his memoir, Heavy: An American Memoir, was released in October 2018.